The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/brv.12762
|View full text |Cite
|
Sign up to set email alerts
|

Why do males emerge before females? Sexual size dimorphism drives sexual bimaturism in insects

Abstract: Conspecific females and males often follow different development trajectories which leads to sex differences in age at maturity (sexual bimaturism, SBM). Whether SBM is typically selected for per se (direct selection hypothesis) or merely represents a side-effect of other sex-related adaptations (indirect selection hypothesis) is, however, still an open question. Substantial interspecific variation in the direction and degree of SBM, both in invertebrates and vertebrates, calls for multi-species studies to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 228 publications
(95 reference statements)
2
45
0
Order By: Relevance
“…Regarding sex, female BSFs, in general, were significantly heavier than their male counterparts in almost all life-history traits except adult mass, but males matured and emerged before females. Males emerging before their female counterparts (protandry) has been confirmed as the dominant form of sexual bimaturism in insects (Teder et al, 2021). The study by Jones and Tomberlin (2019) on BSF larvae found similar results in all studied life-history traits, excluding adult mass, where the effect of sex was also found to be significant.…”
Section: Discussionsupporting
confidence: 51%
“…Regarding sex, female BSFs, in general, were significantly heavier than their male counterparts in almost all life-history traits except adult mass, but males matured and emerged before females. Males emerging before their female counterparts (protandry) has been confirmed as the dominant form of sexual bimaturism in insects (Teder et al, 2021). The study by Jones and Tomberlin (2019) on BSF larvae found similar results in all studied life-history traits, excluding adult mass, where the effect of sex was also found to be significant.…”
Section: Discussionsupporting
confidence: 51%
“…In particular, longer development confers a higher risk of succumbing to natural enemy attack and dying without leaving any progeny (Stearns 1992;Blanckenhorn 2000). Development time effects on fitness may also result from the trade-off between development time and body size: larger individuals are generally more fecund within species (Honek 1993), whereas-everything else being equal-attaining a larger size requires a longer (and riskier) juvenile development (Blanckenhorn 2000;Tammaru et al 2010;Teder et al 2021). Therefore, knowledge of sex-specific responses in development time can also shed further light on environmentally induced variation in sexual size dimorphism (Teder and Tammaru 2005;Hirst et al 2015).…”
Section: Impact Summarymentioning
confidence: 99%
“…To obtain a metric for comparing the thermal sensitivity of male and female development times, we calculated the reduced major axis (RMA) regression slope of male development times on female development times for each primary dataset. The RMA regression slope is a widely used quantitative measure to compare sex-specific plastic responses of various traits across environments (e.g., Fairbairn 1997;Hirst et al 2015;Teder et al 2021). The paired measurements of male and female average development times from each temperature treatment entered these regression models as individual data points.…”
Section: Operations With Primary Datamentioning
confidence: 99%
“…Therefore, the identification and functional study of antennal sensilla are essential to better understand the sensing system in the parasitic wasps and further study the interaction among host plant, pest, and their parasitoids. In general, sexual morphology dimorphism is considered to be a common phenomenon in insect, such as sexual size dimorphism (Teder et al, 2021), sexual wing dimorphism (Matsushima & Yokoi, 2022), and sexual antennae dimorphism (Mariette et al, 2021).…”
Section: Discussionmentioning
confidence: 99%